(No) Time for Change: When and Why Entrepreneurs Act During Underperforming Fundraising Attempts - Wilhelm, Hendrik; Steigenberger, Norbert; Weber, Clarissa E.; Juntunen, Jouni K.; Ebers, Mark (Organization Science, 2024)
Entrepreneurs need to mobilize funds, but they do so under considerable uncertainty about resource holders’ preferences, leading often to fundraising attempts that perform below entrepreneurs’ aspirations. Past research has offered contrasting theorizing and evidence for why entrepreneurs then make changes to their product offering during such attempts as well as for why entrepreneurs refrain from taking such action. This paper develops and tests behavioral theory to reconcile this tension, explicating when and why entrepreneurs change their product offering during underperforming fundraising attempts. Specifically, we argue that entrepreneurs draw on three sources of information that are inherent to fundraising attempts and that inform the extent of their actions to change their product offering: the degree to which they perform below their own fundraising aspirations, the degree to which they fall below peer fundraising performance, and the time that remains until the deadline for the fundraising attempt. Longitudinal data on 576 fundraising campaigns (6,758 observations) published on the crowdfunding platform Kickstarter support our theory. By developing novel behavioral theory on when and why entrepreneurs take action during resource mobilization, we offer contributions to research on entrepreneurial resource mobilization, the crowdfunding literature, and the Behavioral Theory of the Firm. Funding: This work was supported by KölnAlumni. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2020.13803 .